O diagnóstico organizacional para implementação da gestão do conhecimento em uma empresa pública - Tubamoto, Erick; Chiaremonti, Thiago Leonardi (Universidade Federal de São Carlos, 2024)
The organizational diagnosis highlights the crucial need for Knowledge Management in organizations, emphasizing the lack of its widespread practice, which hinders business progress. In the current context of rapid technological evolution and intense competition, knowledge is recognized as a strategic resource to drive innovation and competitive advantage. It highlights the importance of human capital and the involvement of senior management in the implementation of Knowledge Management. The public sector faces challenges such as cultural resistance and lack of infrastructure. The objective of this Final Course Work is, based on an organizational diagnosis, to identify the practices and tools of Knowledge Management, and to identify the strategic gains of the organization after the beginning of the implementation of Knowledge Management implemented in a public organization, which began its implementation of Knowledge Management in a pilot project applied in an operational sector, and later, applied to twelve other departments of the company. For this purpose, a questionnaire was adopted for the analysts and managers of the organization, and their respective views and opinions regarding the results observed after the implementation of Knowledge Management, allowing a comparative analysis of responses from analysts and managers, and a complete visualization of the main gains and bottlenecks present in this project.
Organizational diagnosis for implementing knowledge management in a public company
Keywords: Gestão do Conhecimento; Empresa Pública; Diagnóstico Organizacional; Knowledge Management; Public Company; Organizational Diagnosis; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DE RECURSOS HUMANOS